2020
DOI: 10.1186/s12931-020-01354-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline symptoms and health status on COPD exacerbations in the FLAME study

Abstract: Background: COPD is a heterogeneous disease and patients may respond differently to therapies depending on baseline symptom burden. Methods: This post-hoc analysis from the 52-week FLAME study investigated the impact of baseline symptom burden in terms of health status, dyspnoea, bronchitis status, eosinophil levels and smoking status on the subsequent risk of moderate or severe exacerbations. Health status was measured by St. George's Respiratory Questionnaire (SGRQ) score (higher ≥46.6 and lower < 46.6) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…19,20 The frequency of AECOPD events has previously been tied to a decline in patient-reported quality of life, though over longer durations 7,9,21,22 as time from recovery to baseline from an index exacerbation is estimated at 91 days. 23 These events are associated with low baseline patient-reported quality of life and lung function, 24,25,26 as our study corroborates, and associated with the development of a frequent-exacerbator phenotype. 27,28 One prior study reports similar findings, including the contrast between improvement in patients without exacerbations compared to a stepwise worsening in patients with an increasing frequency of exacerbations, but like other trials, this was observed over at least 52 weeks.…”
Section: Resultssupporting
confidence: 78%
“…19,20 The frequency of AECOPD events has previously been tied to a decline in patient-reported quality of life, though over longer durations 7,9,21,22 as time from recovery to baseline from an index exacerbation is estimated at 91 days. 23 These events are associated with low baseline patient-reported quality of life and lung function, 24,25,26 as our study corroborates, and associated with the development of a frequent-exacerbator phenotype. 27,28 One prior study reports similar findings, including the contrast between improvement in patients without exacerbations compared to a stepwise worsening in patients with an increasing frequency of exacerbations, but like other trials, this was observed over at least 52 weeks.…”
Section: Resultssupporting
confidence: 78%
“…However, further studies have since been published that further support the prognostic factors identified here. For example, recent studies have reported an increased risk of exacerbations in patients with a history of exacerbations [ 105 ], comorbidities [ 106 ], poorer lung function (GOLD stage) [ 105 ], higher symptomatic burden [ 107 ], female sex [ 105 ], and lower BMI [ 106 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the increased CAT score is associated with dyspnea 28,29 and acute exacerbation state or its future risk. [11][12][13][29][30][31] Whilst it is known that FEV 1 has a weak correlation with CAT score, 12,28 several studies have shown a correlation between total CAT scores and GOLD grades. 12,29 In our study, we also found a correlation between total CAT scores and the degree of airflow limitation and DLco.…”
Section: Discussionmentioning
confidence: 99%